PSYCHOMETRIC ANALYSIS OF PERSONAL REPORT OF CONFIDENCE AS SPEAKER USING ITEM RESPONSE THEORY - Hidalgo, Mª Dolores; López Pina, José Antonio; Inglés Saura, Cándido José; Méndez Carrillo, Francisco Xavier (Anales de Psicología / Annals of Psychology, 2002)
The responses of 799 subjects to 30 items, of the Personal Report of Confidence as Speaker (PRCS; Paul, 1966; Bados, 1986) speech anxiety scale were analyzed in an item response framework, using polytomous models. The generalized partial credit model (Muraki, 1992) was applied. The results indicated that the items satisfy the assumptions of generalized partial credit model. Moreover, measurement precision across latent trait levels are presented. Finally, item information function in order to examine the contribution of each item on test information function are showed.